Pengaruh Penggunaan Plastik Sekali Pakai Terhadap Polusi di Lingkungan SD 081/IX Air Itam Kabupaten Muaro Jambi - Ponirah Ponirah (Universitas Batanghari Jambi, 2021)
this research was conducted at SD 081 / IX Air Itam. This research aims to determine the effect of using single-use plastics on environmental pollution. The method used is a quantitative method. The data collection technique used primary data in the form of a test of knowledge about the use of single-use plastic waste and pollution in SD 081 / IX Air Itam. The population in this study were students of class V and VI SD 081 / IX Air Itam, totaling 97 students. Data analysis techniques in this study using simple linear regression analysis techniques using SPSS version 24.0, with the provisions of Sig <α (0.05), H0 is rejected with H1 accepted (significant regression coefficient). Sig> α (0.05), H0 is accepted and H1 is rejected (the regression coefficient is not significant). The results of the overall research X variable (Use of single-use plastic) the majority of respondents got a score of 57 to 73 or 60.82% of the number of respondents. This means that the use of single-use plastics for grade V and VI SD 081 / IX Air Itam is quite good. In the Y variable (Environmental Pollution) scores 74-100 or 94.84%. This means that the understanding of pollution in the environment at SD 081 / IX Air Itam is quite good.